Question and Answers Forum

All Questions      Topic List

Geometry Questions

Previous in All Question      Next in All Question      

Previous in Geometry      Next in Geometry      

Question Number 193686 by Rupesh123 last updated on 18/Jun/23

Answered by mr W last updated on 18/Jun/23

Commented by mr W last updated on 18/Jun/23

c=(√(a^2 +b^2 ))  R=a+b  R^2 =b^2 +c^2 −2bc cos (α+θ)  a^2 +b^2 +2ab=b^2 +a^2 +b^2 −2b(√(a^2 +b^2 )) cos (α+θ)  b−2a=2(√(a^2 +b^2 )) cos (α+θ)  b−2a=2(√(a^2 +b^2 )) (cos α cos θ−sin α sin θ)  b−2a=2 (b cos θ−a sin θ)  a sin θ−((2a−b)/2)=b cos θ  a^2  sin^2  θ−(2a−b)a sin θ+(((2a−b)^2 )/4)=b^2 −b^2 sin^2  θ  (a^2 +b^2 ) sin^2  θ−(2a−b)a sin θ+((4a^2 −4ab−3b^2 )/4)=0  sin θ=(1/(2(a^2 +b^2 )))[a(2a−b)+(√(a^2 (2a−b)^2 −(a^2 +b^2 )(4a^2 −4ab−3b^2 )))]  Area=((c^2  sin θ)/2)=(1/4)[a(2a−b)+b(√(4a(2a−b)−b^2 ))]

$${c}=\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} } \\ $$$${R}={a}+{b} \\ $$$${R}^{\mathrm{2}} ={b}^{\mathrm{2}} +{c}^{\mathrm{2}} −\mathrm{2}{bc}\:\mathrm{cos}\:\left(\alpha+\theta\right) \\ $$$${a}^{\mathrm{2}} +{b}^{\mathrm{2}} +\mathrm{2}{ab}={b}^{\mathrm{2}} +{a}^{\mathrm{2}} +{b}^{\mathrm{2}} −\mathrm{2}{b}\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} }\:\mathrm{cos}\:\left(\alpha+\theta\right) \\ $$$${b}−\mathrm{2}{a}=\mathrm{2}\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} }\:\mathrm{cos}\:\left(\alpha+\theta\right) \\ $$$${b}−\mathrm{2}{a}=\mathrm{2}\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} }\:\left(\mathrm{cos}\:\alpha\:\mathrm{cos}\:\theta−\mathrm{sin}\:\alpha\:\mathrm{sin}\:\theta\right) \\ $$$${b}−\mathrm{2}{a}=\mathrm{2}\:\left({b}\:\mathrm{cos}\:\theta−{a}\:\mathrm{sin}\:\theta\right) \\ $$$${a}\:\mathrm{sin}\:\theta−\frac{\mathrm{2}{a}−{b}}{\mathrm{2}}={b}\:\mathrm{cos}\:\theta \\ $$$${a}^{\mathrm{2}} \:\mathrm{sin}^{\mathrm{2}} \:\theta−\left(\mathrm{2}{a}−{b}\right){a}\:\mathrm{sin}\:\theta+\frac{\left(\mathrm{2}{a}−{b}\right)^{\mathrm{2}} }{\mathrm{4}}={b}^{\mathrm{2}} −{b}^{\mathrm{2}} \mathrm{sin}^{\mathrm{2}} \:\theta \\ $$$$\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} \right)\:\mathrm{sin}^{\mathrm{2}} \:\theta−\left(\mathrm{2}{a}−{b}\right){a}\:\mathrm{sin}\:\theta+\frac{\mathrm{4}{a}^{\mathrm{2}} −\mathrm{4}{ab}−\mathrm{3}{b}^{\mathrm{2}} }{\mathrm{4}}=\mathrm{0} \\ $$$$\left.\mathrm{sin}\:\theta=\frac{\mathrm{1}}{\mathrm{2}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} \right)}\left[{a}\left(\mathrm{2}{a}−{b}\right)+\sqrt{{a}^{\mathrm{2}} \left(\mathrm{2}{a}−{b}\right)^{\mathrm{2}} −\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} \right)\left(\mathrm{4}{a}^{\mathrm{2}} −\mathrm{4}{ab}−\mathrm{3}{b}^{\mathrm{2}} \right.}\right)\right] \\ $$$${Area}=\frac{{c}^{\mathrm{2}} \:\mathrm{sin}\:\theta}{\mathrm{2}}=\frac{\mathrm{1}}{\mathrm{4}}\left[{a}\left(\mathrm{2}{a}−{b}\right)+{b}\sqrt{\mathrm{4}{a}\left(\mathrm{2}{a}−{b}\right)−{b}^{\mathrm{2}} }\right] \\ $$

Commented by Rupesh123 last updated on 18/Jun/23

[1] check last two lines (1/2 ? --> 1/4 ) [2] simplify last radical

Commented by Mingma last updated on 18/Jun/23

It's been a while sir! Neat work!

Commented by Rupesh123 last updated on 18/Jun/23

Perfect ��

Commented by ajfour last updated on 20/Jun/23

P(rcos φ, rsin φ)  r=a+b  r^2 cos^2 φ+(rsin φ−b)^2 =a^2 +b^2   ⇒  2ab+b^2 =2brsin φ  &  altitude of △ is ⊥ to base, so  ((rsin φ)/(rcos φ−a))=((a+rcos φ)/(2b−rsin φ))  ⇒  2brsin φ=r^2 −a^2   consider  (x/a)+(y/b)=1  or   bx+ay−ab=0  let   h=((∣brcos φ+arsin φ−ab∣)/( (√(a^2 +b^2 ))))  c=(√(a^2 +b^2 ))  rsin φ=a+(b/2)  h=((∣b(√((a+b)^2 −(a+(b/2))^2 ))+a^2 −((ab)/2)∣)/( (√(a^2 +b^2 ))))  △=((ch)/2)  =(b^2 /2)∣(√((3/4)+(a/b)))+(a^2 /b^2 )−(a/(2b))∣

$${P}\left({r}\mathrm{cos}\:\phi,\:{r}\mathrm{sin}\:\phi\right) \\ $$$${r}={a}+{b} \\ $$$${r}^{\mathrm{2}} \mathrm{cos}\:^{\mathrm{2}} \phi+\left({r}\mathrm{sin}\:\phi−{b}\right)^{\mathrm{2}} ={a}^{\mathrm{2}} +{b}^{\mathrm{2}} \\ $$$$\Rightarrow\:\:\mathrm{2}{ab}+{b}^{\mathrm{2}} =\mathrm{2}{br}\mathrm{sin}\:\phi \\ $$$$\&\:\:{altitude}\:{of}\:\bigtriangleup\:{is}\:\bot\:{to}\:{base},\:{so} \\ $$$$\frac{{r}\mathrm{sin}\:\phi}{{r}\mathrm{cos}\:\phi−{a}}=\frac{{a}+{r}\mathrm{cos}\:\phi}{\mathrm{2}{b}−{r}\mathrm{sin}\:\phi} \\ $$$$\Rightarrow\:\:\mathrm{2}{br}\mathrm{sin}\:\phi={r}^{\mathrm{2}} −{a}^{\mathrm{2}} \\ $$$${consider}\:\:\frac{{x}}{{a}}+\frac{{y}}{{b}}=\mathrm{1} \\ $$$${or}\:\:\:{bx}+{ay}−{ab}=\mathrm{0} \\ $$$${let}\:\:\:{h}=\frac{\mid{br}\mathrm{cos}\:\phi+{ar}\mathrm{sin}\:\phi−{ab}\mid}{\:\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} }} \\ $$$${c}=\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} } \\ $$$${r}\mathrm{sin}\:\phi={a}+\frac{{b}}{\mathrm{2}} \\ $$$${h}=\frac{\mid{b}\sqrt{\left({a}+{b}\right)^{\mathrm{2}} −\left({a}+\frac{{b}}{\mathrm{2}}\right)^{\mathrm{2}} }+{a}^{\mathrm{2}} −\frac{{ab}}{\mathrm{2}}\mid}{\:\sqrt{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} }} \\ $$$$\bigtriangleup=\frac{{ch}}{\mathrm{2}} \\ $$$$=\frac{{b}^{\mathrm{2}} }{\mathrm{2}}\mid\sqrt{\frac{\mathrm{3}}{\mathrm{4}}+\frac{{a}}{{b}}}+\frac{{a}^{\mathrm{2}} }{{b}^{\mathrm{2}} }−\frac{{a}}{\mathrm{2}{b}}\mid \\ $$

Terms of Service

Privacy Policy

Contact: info@tinkutara.com